Whole-pelvic irradiation with boost to involved nodes and prostate in node-positive prostate cancer - long-term data from the prospective PLATIN-2 trial - Fink, Christoph Andreas; Wegener, D.; Sauer, Lukas; Jäkel, Cornelia; Zips, D.; Debus, Jürgen; Herfarth, Klaus; Körber, Stefan A. (Strahlentherapie und Onkologie, 2024)
Purpose: Node-positive prostate cancer is a potentially curable disease. Definitive radiotherapy to the prostate and lymphatic drainage is an effective treatment option but prospective long-term outcome data are scarce. Thus, the current study aimed to evaluate the toxicity and efficacy of definitive radiation therapy for men with prostate cancer and nodal metastases using modern irradiation techniques. Methods: A total of 40 treatment-naïve men with node-positive prostate cancer were allocated to the trial. All patients received definitive radiation therapy at two German university hospitals between 2009 and 2018. Radiation was delivered as intensity-modulated radiation therapy (IMRT) with 51Gy to the lymphatic drainage with simultaneous integrated boost (SIB) up to 61.2Gy to involved nodes and 76.5Gy to the prostate in 34 fractions. Feasibility and safety, overall and progression-free survival, toxicity, and quality of life measurements were analyzed. Results: During a median follow-up of 79 months, median overall survival was 107 months and progression-free survival was 78 months. Based on imaging follow-up, no infield relapse was reported during the first 24 months of follow-up. There were 3 (8%) potentially treatment-related grade 3 toxicities. Common iliac node involvement was associated with a higher risk of progression (HR 15.8; 95% CI 2.1–119.8; p= 0.007). Conclusion: Definitive radiation to the lymphatic drainage with SIB to the involved nodes and prostate is a safe and effective treatment approach for patients with treatment-naïve, node-positive prostate cancer with excellent infield tumor control rates and tolerable toxicity. Location rather than number of involved nodes is a major risk factor for progression.